"Dual Drainage" in the mixed variety of totally anomalous pulmonary venous connection. Issue 8 (20th May 2021) - Nagulakonda, Sravan; Pandey, Niraj Nirmal; Malhi, Amarinder Singh; Khurana, Rishabh; Arvind, Balaji; Kumar, Sanjeev; Kothari, Shyam Sunder
Abstract: We report a case of 6‐week‐old boy with a mixed variety of totally anomalous pulmonary venous connection where the common channel had a dual drainage into the coronary sinus and left brachiocephalic vein respectively. The case also highlights the role of preoperative computed tomography angiography in demonstrating the exact pulmonary venous anatomy, course and identifying obstruction, when present.